Official journal (League of Nations documents and publications, 1919-1946)
Included are the Minutes (or Procès-verbal) of the Council; the Budget; statements of the "Present situation as regards international engagements registered with the Secretariat"; Saar basin, periodical and other reports and papers; reports on the financial reconstruction of Austria and of Hungary; and many other reports and papers.